2019
DOI: 10.1016/j.htct.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thalassemia major and diabetes mellitus patients at a reference center in Brazil

Abstract: Objective This is a quantitative transversal study that aimed to analyze the sociodemographic and clinical characteristics of thalassemia major patients with and without diabetes mellitus. Method The cohort consisted of 31 thalassemia major patients from a reference center of treatment in Brazil in 2016. The data were obtained from an interview using a questionnaire containing demographic and clinical variables. The results show that 16.1% of the participants with thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However a study found 16.1% of thalassemic patients had diabetes. 19 Another study noted that the incidence of diabetes in thalassemia children was 17.5%. 9 Frequency of first cousin consanguinity was 100 (67 %) and of 2 nd cousin were 48 (33 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However a study found 16.1% of thalassemic patients had diabetes. 19 Another study noted that the incidence of diabetes in thalassemia children was 17.5%. 9 Frequency of first cousin consanguinity was 100 (67 %) and of 2 nd cousin were 48 (33 %).…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study state that there may be role of deficiency of insulin, dysfunction of liver and genetic impact of consanguinity that may start in early. 11,19 Additionally a study found that due to regular transfusions, pancreatic iron may cause impaired glucose tolerance and overt diabetes. 9 Limitations: Study has no information of iron load, only estimated via the iron take through transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The damage sustained by β-cells under iron overload in TDT and NTDT impairs insulin production and leads to hyperglycemia and diabetes. Iron overload also negatively alters the proper functioning of pancreatic β-cells and reduces their insulin production capacity early on during the development of glucose intolerance [20]. Iron overload in β-thalassemia patients could lead to insulin resistance, where elevated blood sugar levels develop because of diminished responsiveness to insulin.…”
Section: Possible Links Between β-Thalassemia and Diabetesmentioning
confidence: 99%
“…1). Therefore, long-term monitoring and management are essential to delay or mitigate anemia, skeletal deformities, heart failure, and diabetes among other complications [18][19][20]. This article aims to review the evidence linking diabetes with β-thalassemia major and explore the utility of early prediction biomarkers and the mechanism(s) underlying this association.…”
Section: Introductionmentioning
confidence: 99%
“…The toxic effect of iron accumulation in beta and acinar cells of pancreas in addition to peripheral resistance to insulin can be the main mechanism through which patients with BTM develop diabetes. 7 However, most of the alterations that occurred in the pancreas are caused by an iron overload which has not been accentuated using chelators. The prevalence of diabetes mellitus in patients with BTM varies from 9.7% to 29%.…”
mentioning
confidence: 99%